“One-click-dialling” design principles and an intelligent recognition algorithm based on a mobile intelligent terminal - Pang, Sulin; Li, Zhijian (Computer communications, 2020)
This article focuses on the implementation of “one-click-dialling” (OCD) based on a mobile intelligent terminal. The design principles of OCD are elucidated for the first time and the concepts of multi-layer mapping, polysemy function, and getting value, etc. are proposed. By analysing a bijection between the mobile phone card and the dialling phone, it innovatively studies two different situations about local OCD and remote roaming OCD. It constructs a functional mapping relation of OCD and establishes the functional mapping relationships in local OCD and in remote roaming OCD, respectively. It is used for recognising which city (or region) the user is in. Furthermore, the paper studies an intelligent recognition algorithm of OCD and uses it for implementing intelligent dialling. The innovative method is applied to the emergency rescue calls of existing government, society, enterprises, and individuals in China, such as 110, 119, 120, 122, government emergency office, social rescue organisations, insurance companies, emergency rescue companies starting with 400, other emergency rescue institutions, etc. The research allows users to call a certain country, no matter which city (or region) they are in when dialling, so they do not waste dialling the emergency rescue department on an intelligent mobile using one-by-one for dialling. The user can directly click the call buttons on the OCD system which have pre-designated the telephone numbers of the locate emergency rescue institution for OCD. The research has practical significance for those interested in social security management.